American grown [compact disc, abridged] : the story of the White House kitchen garden and gardens across America - Obama, Michelle, 1964- (Random House Audio, 2012)
Michelle Obama, the First Lady of the United States, describes how she and her daughters planted a vegetable garden on the White House's South Lawn as part of an initiative to raise awareness about childhood obesity. In February 2010, she launched Let's Move!, a nationwide initiative to address the epidemic of childhood obesity by bringing healthier food into schools and communities, and encouraging kids to be more active. Her book speaks to these issues and also includes practical ideas, recipes, and resources as well as tips on how to begin a garden of any size, anywhere, how to support local farmers' markets, and advice for making healthier food choices.